Interiors of Terrestrial Planets in Metric-Affine Gravity - Aleksander Kozak; Aneta Wojnar (Universe, 2021)
Using a semiempirical approach, we show that modified gravity affects the internal properties of terrestrial planets, such as their physical characteristics of a core, mantle, and core–mantle boundary. We also apply these findings for modeling a two-layer exoplanet in Palatini <semantics>f(R)</semantics> gravity.